Frequency, impact and a preclinical study of novel ERBB gene family mutations in HER2-positive breast cancer. (12th July 2018) - Elster, Naomi; Toomey, Sinead; Fan, Yue; Cremona, Mattia; Morgan, Clare; Weiner Gorzel, Karolina; Bhreathnach, Una; Milewska, Malgorzata; Murphy, Madeline; Madden, Stephen; Naidoo, Jarushka; Fay, Joanna; et al.
Background: Somatic mutations in the ERBB genes (epidermal growth factor receptor: EGFR, ERBB2, ERBB3, ERBB4 ) promote oncogenesis and lapatinib resistance in metastatic HER2+ (human epidermal growth factor-like receptor 2) breast cancer in vitro . Our study aimed to determine the frequency of mutations in four genes: EGFR, ERBB2, ERBB3 and ERBB4 and to investigate whether these mutations affect cellular behaviour and therapy response in vitro and outcomes after adjuvant trastuzumab-based therapy in clinical samples. Methods: We performed Agena MassArray analysis of 227 HER2+ breast cancer samples to identify the type and frequency of ERBB family mutations. Of these, two mutations, the somatic mutations ERBB4 -V721I and ERBB4 -S303F, were stably transfected into HCC1954 (PIK3CA mutant), HCC1569 (PIK3CA wildtype) and BT474 (PIK3CA mutant, ER positive) HER2+ breast cancer cell lines for functional in vitro experiments. Results: A total of 12 somatic, likely deleterious mutations in the kinase and furin-like domains of the ERBB genes (3 EGFR, 1 ERBB2, 3 ERBB3, 5 ERBB4 ) were identified in 7% of HER2+ breast cancers, with ERBB4 the most frequently mutated gene. The ERBB4 -V721I kinase domain mutation significantly increased 3D-colony formation in 3/3 cell lines, whereas ERBB4 -S303F did not increase growth rate or 3D colony formation in vitro . ERBB4-V721I sensitized HCC1569 cells (PIK3CA wildtype) to the pan class I PI3K inhibitor copanlisib but increased resistance to the pan-HER family inhibitor afatinib. The combinations of copanlisib with trastuzumab, lapatinib, or afatinib remained synergistic regardless of ERBB4 -V721I or ERBB4 -S303F mutation status. Conclusions: ERBB gene family mutations, which are present in 7% of our HER2+ breast cancer cohort, may have the potential to alter cellular behaviour and the efficacy of HER- and PI3K-inhibition.